Frama-C: A Software Analysis Perspective - Cuoq, Pascal; Kirchner, Florent; Kosmatov, Nikolai; Prevosto, Virgile; Signoles, Julien; Yakobowski, Boris (Software Engineering and Formal Methods, 2012)
Frama-C is a source code analysis platform that aims at conducting verification of industrial-size C programs. It provides its users with a collection of plug-ins that perform static analysis, deductive verification, and testing, for safety- and security-critical software. Collaborative verification across cooperating plug-ins is enabled by their integration on top of a shared kernel and datastructures, and their compliance to a common specification language. This foundational article presents a consolidated view of the platform, its main and composite analyses, and some of its industrial achievements.